The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1159/000469706
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Remote and Bedside Assessment of the National Institute of Health Stroke Scale in Acute Stroke Patients

Abstract: Introduction: Telestroke videoconference for conducting the National Institute of Health Stroke Scale (NIHSS) is recommended when the facility of a direct bedside evaluation by a stroke specialist is not immediately available for hyperacute stroke assessment. However, some NIHSS-telestroke studies inherit systematic bias due to the subjective nature of NIHSS administration. We aimed to evaluate NIHSS telestroke assessment, while implementing measures to minimize subjectivity bias. Patients and Methods: Ninety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 13 publications
3
13
0
Order By: Relevance
“…A study found that lack of proper infrastructure or road access in rural areas may significantly lengthen OTT time, thus contributing to the low rate of thrombolysis (Alasheev et al, 2017). Telemedicine helps to address this delay by allowing neurologists from stroke centers to perform quick assessment, triage, and give emergency treatment advices to EMS dispatchers even before patients' arrival at the hospital (Jauch et al, 2013)-as shown by a reduction of roughly half an hour when compared to conventional EMS (Helwig et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A study found that lack of proper infrastructure or road access in rural areas may significantly lengthen OTT time, thus contributing to the low rate of thrombolysis (Alasheev et al, 2017). Telemedicine helps to address this delay by allowing neurologists from stroke centers to perform quick assessment, triage, and give emergency treatment advices to EMS dispatchers even before patients' arrival at the hospital (Jauch et al, 2013)-as shown by a reduction of roughly half an hour when compared to conventional EMS (Helwig et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The National Institutes of Health Stroke Scale can be performed efficiently via telemedicine. 9 Televideo is superior to telephone. 10 Yet, telephonic consultation is superior to no consult.…”
Section: Telemedicinementioning
confidence: 99%
“…Meanwhile, telemedicine was also being used for other neurologic disorders such as epilepsy [2]. The main field of development for telemedicine is in acute stroke care and reliability of telestroke after remote examination of stroke patients by audio-visual connection is well established [3][4][5] by testing stroke scales. However, results of studies in telestroke service cannot be generalized into other fields of neurology [6].…”
Section: Introductionmentioning
confidence: 99%